DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN IDENTITAS DIRI REMAJA PUTRI SMK AL MANAAR MUHAMMADIYAH PEMALANG - ita nur itsna; Yessy Pramita Widodo; Rahmasari Rahmasari (Bhamada: Jurnal Ilmu dan Teknologi Kesehatan (E-Journal), 2021)
Adolescence is the most unique period, a period that can be said to be the most critical period in development at the next stage of life. In adolescence, the formation of self-identity is very important because adolescents have a unique way of dealing with life. Providing social support during adolescence is very much needed, especially for adolescents who are in the search for self-identity. Providing social support can be provided by people closest to the youth environment. The environment plays a big role in shaping adolescent behavior. The purpose of this study was to determine the relationship between peer social support and self-identity of young women at SMK Al Manaar Muhammadiyah Pemalang. This study uses the correlation method with a cross-sectional approach. The number of samples in this study was 30 with a total sampling technique. Respondents are XI grade students of SMK Al Manaar Muhammadiyah Pemalang. The results showed that there was a significant relationship between peer social support and self-identity of young women with a p value of 0.001 (<0.05). Teens are expected to provide support to each other both in terms of emotional, material, appreciation, and other support to improve self-identity.